Unlocking Access to Climate Finance for Pacific Island Countries - Fouad, Manal; Novta, Natalija; Preston, Gemma; Schneider, Todd. (Washington, D.C. : International Monetary Fund, 2021)
This departmental paper provides an in-depth overview of access to climate finance for Pacific Island Countries, evaluating successes and challenges faced by countries and proposes a way forward to unlock access to climate funds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate Change, Pacific Islands, Climate Finance and Public Financial Management; Climate; GCF Requirement; Global Warming; Natural Disasters and Their Management